Myanmar: Impacts of COVID-19 on Economy, Agri-Food Systems, Jobs & Incomes - Diao, Xinshen; Aung, Nilar; Lwin, Wuit Yi; Zone, Phoo Pye; Thurlow, James; Nyunt, Khin Maung (2020)
Myanmar: Impacts of COVID-19 on Economy, Agri-Food Systems, Jobs & Incomes Feed the Future Myanmar Agriculture Policy Support Activity (MAPSA) Policy Note Updated: June 4, 2020